(untitled) (Applied Biological Research, 2015)
The present study was aimed to detect Mycoplasma spp. associated with the female reproductive tract of cattle and buffaloes in Punjab (India). Out of 65 samples comprising of uterine discharges, vaginal mucus and foetal stomach contents, 21 were positive for Mycoplasma spp. by genus specific PCR using primers based on 16S rDNA of Mycoplasma spp. An amplification band of 270-bp was obtained in all the positive samples. The overall prevalence of Mycoplasma spp. in cattle and buffaloes was 32.3% whereas the prevalence was 24.61 and 7.69% in cattle and buffaloes, respectively. Maximum prevalence of 21.7% was seen in HF breed of cattle and 15.78% in Murrah breed of buffaloes. Cattle and buffaloes in age group 4-6 years and 6-8 years were found more positive for Mycoplasma spp.